Self-denail about Malamatiyyah - شامي أمجد; ميساء علي (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
In a certain time around the middle of the thirteenth century of the Prphit migration. Malamaty was existed, its people were distanced from those psychos whom we can find every once while during history. Those who used to exaggerate to blame themselves for smaller things before the diggers and unwillingly which refers to religion customs, or their psycholigisalasel and social composition. That made them considered as psychos and nutts. But Malamatists were different who started blaming themselves in order to improve it and get the best of it. They were effected by the idea that considers the human self as the resource of all evil act and thoughts. They were attracted to youthful believers in religion history .As well as they were related somehow to Sufism which they Took its name then they have applied to. they have shared the Sufism one of its major principals especially what is called self-desire resistance. But malamatist were different from sufists by denying human self in order to fix it and get the best of it, not to consider reunion with the Devin soul of God or caring about mortality.